Optimal policy and taylor rule cross-checking under parameter uncertainty - Dirk Bursian; Markus Roth (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2013)
We examine whether the robustifying nature of Taylor rule cross-checking under model uncertainty carries over to the case of parameter uncertainty. Adjusting monetary policy based on this kind of cross-checking can improve the outcome for the monetary authority. This, however, crucially depends on the relative welfare weight that is attached to the output gap and also the degree of monetary policy commitment. We find that Taylor rule cross-checking is on average able to improve losses when the monetary authority only moderately cares about output stabilization and when policy is set in a discretionary way.
urn:nbn:de:hebis:30:3-317864
Keywords: E47; E52; E58; 330; Optimal monetary policy; parameter uncertainty; Taylor rule